(untitled) (International Journal of Food and Nutritional Sciences, 2022)
To evolve the concept of sustainable agriculture, the need for creating SHGs in villages became imperative to uplift the economic and living standards of rural people in general and women in particular (Dwivedi et al., 2019). Development schemes are increasingly advocating for the participation of women in SHGs as they are considered to be critical elements in community programs to increase the participation of rural women, empowering women to take the lead in their own development and strengthen the role and position of women in society (Prabhakar, 2020). An SHG is an informal group bringing together the rural poor, providing a platform for women to interact, share knowledge, and access diverse services(VARALAKSHMI & YOGANANDHAM)The mission of the SHG is to foster collaborative endeavors, internal lending, term deposits, an opening balance of a bank, and availing of small loans at affordable interest rates. (Gnanakumar & Justin, 2021)